Pengaruh Model Pembelajaran Project Based Learning terhadap Hasil Belajar Geografi Siswa SMAN 5 Pamekasan - Desy Triana Dewi Harizah; Sumarmi Sumarmi; Syamsul Bachri (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This research aims to describe the effect of the Project-Based Learning model on geography learning outcomes. This quasi-experimental research used pre-test and post-test. The researcher chose class XI IPS 2 by applying a project-based learning model and XI IPS 3 was treated using a conventional method. Collecting data used essay questions and documentation. The data obtained were analyzed using the gain score. Furthermore, to determine whether there was an effect of the project-based learning model or not, the researcher used the t-test. The results obtained were as follows; the average post-test for the control class was 76.81 and the post-test average for the experimental class was 84.48. While the gain score for the control class was 39.98 and the experimental class was 59.96. It can be concluded that the application of the project-based learning model is effective in improving student learning outcomes.